The Effect of Trade Liberalization on the Growth of Green GDP in Iran Using Gravitational Search Algorithm and the Algorithm Firefly - nahid pourfereidooni; hosein akbarifard; amin Amin Ghaseminezhad (پژوهش‌های برنامه و توسعه)
One of the reason affecting on the national economy is, GDP . But it only covers market value of final goods and services produced in the economy;it is not inclusive negative environmental impacts.On the other hand as a result of trade liberalization, economic activity expanded and use of resources and energy inappropriately increases.So theoretically, demonstrate that GDP is not a good criterion for measuring the economic well-being. Consistently, standards for calculating national income has been proposed to raising the inadequacy of these measures standards, is green GDP. In this study, to evaluate the impact of trade liberalization on green GDP, methods gravitational search algorithm and Firefly algorithm that has been used for some given time in the years 1961- 2015. The results of the evaluation of the impact of trade liberalization show that this variable is positive and significant effect on green GDP. The results show that due to the positive impact of trade liberalization on green GDP, this variable as a variable known to reduce pollution; this means that an increase in trade transactions with Iran will lead to improved environmental quality.